Analisis Semiotika dalam Tradisi Mangalap Tondi di Kecamatan Batang Toru Kabupaten Tapanuli Selatan - Sumayya Sumayya; Asrul Harahap (ARZUSIN, 2026)
Although the mangalap tondi tradition as part of cultural communication has received attention in a number of studies, studies that specifically examine the symbolic meaning of this tradition through Roland Barthes’s semiotic approach remain limited. This study aims to explore and analyze the symbolic meaning in the mangalap tondi tradition among the Batak Angkola community in Batang Toru Subdistrict, South Tapanuli Regency. This study employed a qualitative approach with a descriptive design, involving informants selected purposively. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using the Miles and Huberman data analysis technique, which includes data reduction, data display, and conclusion drawing. The findings show that the symbolic meaning in the mangalap tondi tradition is divided into three main categories, namely object symbols, speech symbols, and action symbols. These three categories contain denotative, connotative, and mythological meanings that represent the community’s belief system regarding the existence of tondi. These findings contribute to the development of semiotic theory in the context of cultural communication while also broadening understanding of the local cultural practices of the Batak Angkola community. This study concludes that symbolic meaning plays an important role in maintaining the sustainability of cultural traditions and underscores the need for efforts to preserve cultural values through deeper understanding. The implications of this study include theoretical contributions to cultural communication studies and practical contributions to local cultural preservation, as well as opening space for further research on the dynamics of changes in cultural meaning in the modern era.